2007
DOI: 10.1002/pd.1783
|View full text |Cite
|
Sign up to set email alerts
|

Workshop report on the extraction of foetal DNA from maternal plasma

Abstract: This workshop initiated a standardization process for extraction of cff DNA in maternal plasma. The highest yield was obtained by the QIAamp DSP Virus Kit, a result that will be evaluated in more detail in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 22 publications
0
78
0
1
Order By: Relevance
“…First successful applications of the EZ1 system, which requires considerable less handson time of technical laboratory assistants than tradition column-based extraction systems [23], were published in the fi elds of microbiology [24] and forensic medicine [25,26] as early as in 2005. The EZ1 system was shown to be useful for the isolation of target DNA in low quantities, e.g., of fetal DNA in maternal plasma [21], or of DNA in partially degraded biological specimens [22]. Successful EZ1-based DNA extraction from formalin-fi xed, paraffi nembedded tissue samples [9], or otherwise long-term preserved tissue specimens [8] has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…First successful applications of the EZ1 system, which requires considerable less handson time of technical laboratory assistants than tradition column-based extraction systems [23], were published in the fi elds of microbiology [24] and forensic medicine [25,26] as early as in 2005. The EZ1 system was shown to be useful for the isolation of target DNA in low quantities, e.g., of fetal DNA in maternal plasma [21], or of DNA in partially degraded biological specimens [22]. Successful EZ1-based DNA extraction from formalin-fi xed, paraffi nembedded tissue samples [9], or otherwise long-term preserved tissue specimens [8] has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Hence, for manual reference methods, it has been demonstrated that the QIAamp DSP Virus Kit might be the optimal tool because it extracts mainly small fragments of DNA, finally providing larger amounts of cffDNA. 30,31 Second, regarding false-positive results, it has been observed that a multicopy sequence, such as DYS14, is more sensitive, accurate, and efficient than the single-copy SRY in the assessment of cffDNA, which is particularly important early in the first trimester of pregnancy when the copy numbers of fetal DNA are low. 32 The drawback of the DYS14 sequence is that it has considerable homology to sequences other than the Y chromosome that could falsely classify female fetuses as male.…”
Section: Genetics In Medicine | Volume 14 | Number 1 | January 2012mentioning
confidence: 99%
“…In particular, RT-MSP of EF3 marker on bisulfite converted plasma DNA samples was carried out assuming that the mean yield of DNA extracted per 0.5 ml of plasma is 10 ng, of which 5% is of fetal origin, as suggested by Legler et al 44 and assuming that the yield of DNA after bisulfite conversion is 65%. To verify the fetal origin of the RT-MSP product from maternal plasma samples we amplified plasma DNA, the corresponding amounts of maternal blood cell DNA and CVS DNA as negative and positive controls respectively.…”
Section: Ef3 Discriminates Cffdna Versus Cfmdna In Maternal Plasma Samentioning
confidence: 99%